Use of Knowledge Transfer Theory to Improve Learning Outcomes of Cognitive and Non-cognitive Skills of University Students: Evidence From Taiwan - Peng, Michael Yao-Ping; Feng, Yongjun; Zhao, Xue; Chong, WeiLoong (Frontiers in Psychology, 2021)
Previous studies have explored a multitude of factors influencing student learning outcomes based on various theories. Knowledge transfer theory was adopted to develop the antecedents of student learning outcomes in the complete learning process. This study aims to explore the conspicuousness between various factors within the structural model, such as knowledge transfer, student orientation and absorptive capacity, by combining marketing and management concepts with higher education studies. This study takes Taiwanese university students as its research samples, and purposive sampling is adopted. A total of 873 questionnaires are collected in this study. PLS-SEM was used to verify the structural relationship in data analysis via running of SmartPLS. The results indicate that knowledge transfer and student orientation have significant impacts on students' absorptive capacity and learning outcomes, and that students’ prior knowledge has a positive moderating effect on the relationship between knowledge transfer and absorptive capacities. Based on these findings, the researchers propose feasible suggestions for related issues and future research.